The Influence of Marketing Content and Brand Image on Vespa Coffee (KOPVES) Purchase Decisions - Riza Ardy Saputra; Siska Ernawati Fatimah (Majapahit Journal of Islamic Finance and Management, 2026)
This study was conducted to analyze "The Influence of Marketing Content and Brand Image on Purchasing Decisions of Vespa Cirebon Coffee." In this study, the author used a questionnaire method as a data collection method and used multiple linear regression as a data analysis method. The research conducted showed that there is a simultaneous positive and quite significant influence that can influence buyers' decisions in choosing a product through marketing content and positive brand image.